The wild ones - London, C. Alexander (New York : Philomel Books, 2015)
After his parents are killed, Kit, a young raccoon, sets off for the city with a stone that may be the key to finding the Bone of Contention, a legendary object that is proof of a deal giving the wild animals the rights to Ankle Snap Alley, which the dogs and cats known as the Flealess want back and are willing to kill for.
Keywords: Animals -- Juvenile fiction; Fantasy fiction